COVID-19 and the Co-production of Social and Government Control Agencies - Borges, Gislaine; Moretto Neto, Luis (Revista de Negócios, 2021)
This article aims to identify the occurrence of co-production of public services between social and government agencies of control, during the fight against COVID-19, in 2020, in Brazil. Having as theoretical and methodological proposal the Theory P of Alberto Guerreiro Ramos, consultations were made in the official websites of two state control institutions - the Office of the Comptroller General (CGU) and the Brazilian Federal Court of Accounts - and three entities representing organized civil society - the Brazilian Social Observatory, the Transparency Brazil and the Transparency International. Based on the collected data (news, newsletters, reports, online information panels, and other publications), a content analysis based on the theoretical framework built was carried out. The results showed that the analyzed organizations have developed initiatives that, individually or in partnership with other institutions, have contributed to reducing the impacts of the current health crisis (COVID-19). The evidence also revealed that the co-production of public services by the agencies of control embraced converges with the meaning of objective possibility postulated by Guerreiro Ramos.